Model United Nations and Deep Learning: Theoretical and Professional Learning. Issue 2 (3rd April 2017) - Engel, Susan; Pallas, Josh; Lambert, Sarah
ABSTRACT: This article demonstrates that the purposeful subject design, incorporating a Model United Nations (MUN), facilitated deep learning and professional skills attainment in the field of International Relations. Deep learning was promoted in subject design by linking learning objectives to Anderson and Krathwohl's (2001 ) four levels of knowledge or cognition: factual, conceptual, procedural, and metacognitive. Students demonstrated improvement in all four areas; however, this article focuses on outcomes in the conceptual and metacognitive realms as these were where students showed the most growth. In the conceptual realm, the subject aimed to increase students' capacity to apply international relations theories. Students tended to utilize the traditional theories of realism and liberalism; however, their explanations and applications of these theories showed deep learning. In the metacognitive realm, students were able to analyze their own negotiation styles and to explain how it influenced their approach to the Model UN, thus demonstrating strong professional skills development and metacognitive growth. Learning was enhanced by the use of open access online subject materials and online communications. The subject was designed and run in a context where simulations in teaching politics and international relations are not common.